How did we find out about DNA? - Asimov, Isaac, 1920-1992.; Wool, David (New York : Walker, 1985)
Describes the discovery of deoxyribonucleic acid, or DNA, a complex molecule found in all cells and which plays a vital part in heredity.
Includes index.
Booklist.
School Library Journal.
Science Books & Films (A.A.A.S.).
6.1
6.1
Keywords: DNA -- History -- Juvenile literature; DNA -- History; DNA -- History